A Longitudinal Analysis of Chlamydial Infection and Trachomatous Inflammation Following Mass Azithromycin Distribution. (2nd January 2019) - Morberg, Daniel P.; Alemayehu, Wondu; Melese, Muluken; Lakew, Takele; Sisay, Alemayehu; Zhou, Zhaoxia; Cevallos, Vicky; Oldenburg, Catherine E; Porco, Travis C; Lietman, Thomas M; Keenan, Jeremy D
ABSTRACT: Background : Mass azithromycin distributions are effective for clearing ocular strains of Chlamydia trachomatis, yet infection frequently returns in areas with hyperendemic trachoma. A better understanding of the factors associated with chlamydial reinfection could be helpful to plan trachoma elimination strategies. Methods : This was a prospective cohort study conducted in a trachoma-hyperendemic region of Ethiopia in 2003. As part of a larger cluster-randomized trial, 21 villages were treated with a single mass azithromycin distribution and all children 5 years and younger were monitored for ocular chlamydia and clinically active trachoma at baseline and at 2 and 6 months following the treatment. Results : In 20 villages with available data, azithromycin treatment coverage was 88.7% (95% confidence interval [CI] 85.7–91.8%). In total, 1005 children tested negative for ocular chlamydia at the 2-month visit, of whom 41 became infected by 6 months (1.0 incident chlamydia infections per 100 person-months, 95%CI 0.7–1.4). The presence of intense trachomatous inflammation (TI) at baseline was associated with incident infection at 6 months (incidence rate ratio 1.91, 95%CI 1.03–3.55). Ocular chlamydia infections clustered more within households than communities: (intraclass correlation coefficient 0.01 for communities and 0.29 for households six months posttreatment). Younger children were more likely to have persistent clinically active trachoma ( P  = 0.03). Conclusions : More intensive antibiotic distributions may be warranted for younger children, for children with TI, and for households containing children with ocular chlamydia infections.